Організація обліку відходів підприємств - Гуріна, Н. В. (Видавництво Львівської політехніки, 2014)
Уточнено класифікаційні ознаки та надано пропозиції щодо вдосконалення організації і методики обліку відходів з урахуванням галузевих особливостей діяльності підприємств. Запропонована методика обліку відходів деревообробних підприємств надасть можливість отримувати повну й достовірну інформацію про відходи за місцями виникнення і зберігання та контролювати ефективність їх використання. The author of the article examines industry of special features of accounting of wastes and analyses their influence on the costs of production. For clear organization of record-keeping an important aspect is classification of wastes. It is expedient to classify them: quality, possibility of the subsequent use, origin. in relation to the stages of production and the types of production. The author of the article examines and suggestions are given in relation to the reflection of wastes in the set of accounts of record-keeping. It is suggested to use the segregated balance account 29 the “Second material resources” for forming of objective informative base about wastes. The information about the places of education and utilization of wastes is very important. It is stipulated the necessity of development (improvement) of primary and current documents of the account of wastes of woodworking enterprises. The specified form is offered primary a document for the reflection of information about wastes by introduction of additional essential elements: columns of humidity, quality and sort of wood. For control of these indexes the place of signature of responsible person is foreseen. The developed forms of the administrative accounting will provide a managerial staff by information about wastes and will influence on efficiency of the accepted decisions in relation to an origin and utilization of wastes. The proposed methods of accounting of wastes for timber industry enterprises give an opportunity to get full and reliable information about wastes in places of their appearing and preservation, to control the efficiency of their use.
Accounting of wastes of enterprises
Keywords: облік відходів; відходи виробництва; вторинні матеріальні ресурси; відходи деревообробки; зворотні відходи; ділові відходи; деревообробні підприємства; accounting of wastes; processing wastes; secondary material resources; wood-working wastes; reverse wastes; business wastes; wood-working enterprises